A soma das raízes da equação 2x²-6x=0 é igual a?
Soluções para a tarefa
Respondido por
2
Soma das raizes = -b/a
Logo:
6/2 = 3
Logo:
6/2 = 3
Respondido por
2
Δ = b² -4ac
Δ = (-6)² -4 *2 * 0
Δ = 36 0
Δ = 36
x' = (-b + √∆)/ 2a
(-(-6) + 6)/2 * 2
(6 + 6)/4
12/4
3
x'' = (-b - √∆)/ 2a
(-(-6) - 6)/2 * 2
(6 - 6)/4
0/4
0
S= 0+3 = 3
Resposta: 3.
Δ = (-6)² -4 *2 * 0
Δ = 36 0
Δ = 36
x' = (-b + √∆)/ 2a
(-(-6) + 6)/2 * 2
(6 + 6)/4
12/4
3
x'' = (-b - √∆)/ 2a
(-(-6) - 6)/2 * 2
(6 - 6)/4
0/4
0
S= 0+3 = 3
Resposta: 3.
Perguntas interessantes
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Filosofia,
1 ano atrás
Física,
1 ano atrás